Plus Ça change French NATO rapproachement - Anderson, Craig A (Monterey, California. Naval Postgraduate School, 1997)
On December 5, 1995, the French government announced its decision to increase its level of participation in NATO. Although France was not rejoining the Alliances integrated military structure, the French Foreign Minister would resume attending meetings of NATOs Military Committee in an official capacity. This decision broke with 30 years of French foreign policy begun by President Charles de Gaulle when he withdrew French forces from NATO in 1966. Why has Paris changed its NATO policy? Officially, the French government stated that it wanted to take an active role in reforming the Alliance after the end of the Cold War and to strengthen the European contribution to North Atlantic security. However, while these were actual French foreign policy goals, achieving them was not the primary reason that France changed its NATO policy. Several events, including the Gulf War and the Bosnian conflict had revealed the weakness of the French military and its inability to carry out French foreign policy objectives. At the same time, the sluggish French economy prevented France from modernizing its forces. Faced with these realities, France had little choice but to expand its ties to NATO in the interest of its own national security Approved for public release; distribution is unlimited. Lieutenant, United States Navy http://archive.org/details/pluschangefrench109458825